2004
DOI: 10.1055/s-2004-813322
|View full text |Cite
|
Sign up to set email alerts
|

Der Einsatz von Methylphenidat im Kindesalter: Analyse des Verordnungsverhaltens auf der Basis von Routinedaten der gesetzlichen Krankenkassen zu Arzneimittelverordungen

Abstract: In Mecklenburg-Vorpommern the prevalence of stimulant treatment has clearly increased. Since diagnosis-related data is not available it is not possible to assess the indications for treatment. Further studies should serve to evaluate the correspondence between diagnosis and therapy in relation to stimulant medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…A lower MPH treatment prevalence of 1.1% was also reported from Hesse in 2007, with an estimate of 1.7% for boys and 0.4% for girls under the age of 18 [2]. These lower prevalence estimates in Mecklenburg-West Pomerania and Hesse may indicate regional variations in MPH treatment in Germany [8]. In our study, treatment prevalence increased steadily from age 6 to age 11, which was also observed in the study from Hesse [2].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A lower MPH treatment prevalence of 1.1% was also reported from Hesse in 2007, with an estimate of 1.7% for boys and 0.4% for girls under the age of 18 [2]. These lower prevalence estimates in Mecklenburg-West Pomerania and Hesse may indicate regional variations in MPH treatment in Germany [8]. In our study, treatment prevalence increased steadily from age 6 to age 11, which was also observed in the study from Hesse [2].…”
Section: Discussionmentioning
confidence: 89%
“…For Germany, MPH treatment prevalence was reported in two regional [2,8] and one national study [6], each based on data from a single health insurance company.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescription data from statutory health insurance (SHI) providers in Germany show a comparable trend 9. The drug prescription report describes a more-than-fivefold increase in prescriptions from 10 million DDDs (defined daily doses) in 1999 to 53 million DDDs in 2008 10.…”
Section: Introductionmentioning
confidence: 99%
“…These concern primarily delays in social, cognitive, and emotional functions, which manifest as symptoms such as difficulties in sleeping and lack of concentration. 1 A study by Schlack et al 2 shows the prevalence of ADHD to be around 5%, with boys affected about four times more often than girls are. While treatment with Ritalin (methylphenidate) is on the rise, 1 the use of body-oriented methods in the treatment of ADHD has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%